A Rapid High Throughput Vibration and Vortex-Assisted Matrix Solid Phase Dispersion for Simultaneous Extraction of Four Isoflavones for Quality Evaluation of Semen Sojae Praeparatum - Yang, Xuejing; Sun, Ali; Boadi, Evans Owusu; Li, Jin; He, Jun; Gao, Xiu-mei; Chang, Yan-xu (Frontiers in Pharmacology, 2020)
soflavones (daidzein, daidzin, genistein and genistin) in Sojae semen praeparatum were simultaneously extracted and quantified by a high throughput Vibration and Vortex-Assisted matrix solid phase dispersion (VVA-MSPD) and high performance liquid chromatography with photodiode array detection. Using single factor tests, parameters influencing extraction efficiency of VVA-MSPD such as sorbent type, sample to sorbent ratio, ball mill crushing time, ball mill vibration frequency, methanol concentration, eluting solvent volume and vortex time were optimized. Under optimal conditions of 2 min crushing time and vibration frequency of 800 times per min; 20 mg Sojae semen praeparatum sample and 40 mg SBA-3 were crushed with ball mill machine. Thereafter, the treated sample was dropped with 1.5 mL Methanol/water (8:2, v/v) by 3 min vortex. Analytical recoveries of the four compounds ranged from 86.1%-94.8% and relative standard deviation (RSD) was less than 5%. A good linearity (r > 0.9994) was achieved with the range 0.5 -125 μg/ml. The established high throughput Vibration and Vortex-Assisted MSPD coupled with high performance liquid chromatography (HPLC) method was user-friendly and displayed high throughput and rapidity compared to normal MSPD and traditional extraction methods